(untitled) (Applied Biological Research, 2019)
Oral submucous fibrosis (OSF) is a chronic inflammatory condition due to areca nut (Areca catechu) chewing which induces fibrosis leading to the difficulty in mouth opening. Various profibrotic cytokines and chemokines have been found involved in fibrosis. The present study was aimed to find the role of interleukin 13 (IL-13) in recruiting the myofibroblasts and as a causative factor for fibrosis in OSF. Twenty-five sections of OSF tissue and ten sections of normal mucosa were stained with IL-13, TGF-β1 and α-SMA antibodies using immunohistochemical method. Immunostaining was done to assess staining intensity and percentage of positive cells. The results were analyzed by SPSS software. The expression of all three markers IL-13, TGF β1 and α-SMA showed significant difference between control and OSF (p < 0.001), control and early OSF (p < 0.001) control and advanced OSF (p < 0.001). No statistical difference was found between early OSF and advanced OSF. Significant expression of IL-13 and its correlation with TGF-β and α SMA suggests its role in pathogenesis of OSF.